Molecular gas observations of the reddened quasar 3C 318 - Willott, C; Martinez-Sansigre, A; Rawlings, S (2006)
3C 318 is a z=1.574 radio-loud quasar. The small physical size of its radio jets indicate that these jets were triggered relatively recently. In addition to the ultraviolet continuum emission being reddened by dust, detections with IRAS and SCUBA show it to have an exceptionally high far-infrared luminosity. We present CO(2-1) observations of 3C 318 made with the IRAM Plateau de Bure Interferometer. We detect CO(2-1) emission with a FWHM=200 km/s at a signal-to-noise ratio of 5.4. There is evidence for positional (~ 20 kpc) and velocity (~ -400 km/s) offsets between the molecular gas and the quasar which may be due to the quasar experiencing a major merger. The mass of molecular gas inferred from our observations is M_{H_2}=(3.0 +/- 0.6) x 10^{10} M_sun. This molecular gas mass is comparable to that in sub-mm-selected galaxies at similar redshifts. The large molecular gas mass is consistent with the primary source of heating for the cool dust in this quasar to be massive star formation with a star formation rate of 1700 M_sun/yr and a gas depletion timescale of 20 Myr. Our observations support the idea that star formation episodes and jet triggering can be synchronised.